Multi‐Step Chemical Solution Deposition‐Annealing Process Toward Wake‐Up Free Ferroelectricity in Y:HfO2 Films. Issue 18 (28th August 2021) - Samanta, Shibnath; Anoop, Gopinathan; Joh, HyunJin; Seol, WooJun; Park, Seong Min; Unithrattil, Sanjith; Lee, Jun Young; Kim, Tae Yeon; Kim, Hoon; Yeom, Jiwon; Hong, Seungbum; Jo, Ji Young
Abstract: Ferroelectricity in HfO2 thin films can be utilized for fast, power‐efficient, and highly scalable non‐volatile memories. However, the required wake‐up process for inducing ferroelectricity/ achieving higher polarization is one of the major hurdles that hinder HfO2 ‐based thin films from developing reliable electronic devices. The wake‐up effect is believed to originate from i) phase transformation from non‐ferroelectric to ferroelectric, ii) movement of defect entities (mainly oxygen vacancy defects) near the film‐electrode interface, and iii) heterogeneity of the electrode interfaces. In the present study, an experimental strategy is designed to overcome these sources of the wake‐up process. A multi‐step deposition and annealing process is carried out to induce wake‐up‐free ferroelectricity in Yttrium doped HfO2 (Y:HfO2 ) thin film directly grown on Si‐substrate. Furnace annealing is utilized instead of the standard rapid thermal annealing process to reduce the oxygen deficiencies and stimulate the direct growth of the polar Y:HfO2 . The oxygen‐vacancy‐related defects are found to be the dominating source of wake‐up effect in Y‐doped HfO2 films. The step‐wise deposition and annealing in the oxygen atmosphere facilitate direct growth of the polar phase, reduce the oxygen vacancies, and induce wake‐up‐free ferroelectricity in Y:HfO2 . Abstract : The ferroelectric wake‐up effect in HfO2 ‐based thin films is caused by oxygen vacancies mainly. The requirement of wake‐up treatment to achieve the maximum remnant polarization is eliminated by reducing the possibility of oxygen deficiency via multi‐step deposition and annealing process. As a result, wake‐up free ferroelectricity is achieved.